DIGITAL COMPETENCIES AND CONTINUING TEACHER EDUCATION: AN ANALYSIS IN LIGHT OF THE BNCC AND CETIC.BR INDICATORS - da Cruz, Amanda Queirolo Ribeiro; Fleury, Patrícia Fonseca Ferreira (Seven Editora, 2026)
This article analyzes teacher education for the use of Digital Information and Communication Technologies (DICT) in the context of digital culture, in light of the main legal documents that guide Brazilian education, such as the Federal Constitution, the Law of Guidelines and Bases of National Education (Lei de Diretrizes e Bases da Educação Nacional – LDB), the National Common Curricular Base (BNCC, 2018), and the National Teacher Education Guidelines (BNC-Formação, 2020). The study is grounded in the problem of understanding how educational policies and teacher education processes can contribute to the critical integration of digital technologies into pedagogical practices, promoting a more inclusive, innovative, and contemporary-oriented education. The objective of the research is to analyze the contributions of teacher education to the integration of DICT into the teaching–learning process, articulating theoretical frameworks, official documents, and empirical data from the ICT Education survey conducted by Cetic.br (2024). The study adopts a qualitative, exploratory, and bibliographic approach, drawing on authors such as Nóvoa, Tardif, Kenski, Moran, and Freire, as well as legislation and guidelines that structure initial and continuing teacher education. Data analysis reveals trends such as the expansion of access to digital technologies in Brazilian schools, the gradual adoption of active methodologies, and the recognition of continuing education as a strategy for strengthening teaching practice. The results indicate that teachers who engage in professional development programs show a greater predisposition toward pedagogical innovation and the critical and intentional use of digital resources. However, the findings also demonstrate that the availability of equipment and connectivity alone does not ensure pedagogical transformation, making teacher mediation and critical reflection essential. Thus, teacher education for the use of DICT is characterized as a critical-reflective and collaborative process, fundamental to strengthening the role of teachers as mediators of learning and agents of educational transformation in the 21st century. DOI: https://doi.org/10.56238/sevened2026.008-040